A study to explore the capacity of family and service providers to facilitate participation of disabled youth in accessing opportunities in skills development and employment in Cofimvaba, Eastern Cape - Ned-Matiwane, Lieketseng (Department of Health and Rehabilitation Sciences, 2015)
Includes abstract.